A fábrica de deuses: o universo e sua função essencial na filosofia de Henri Bergson - Luiz, Rauan de Oliveira (Universidade Federal de São Carlos, 2020)
The last sentence of Les deux sources de la morale et de la religion, Henri Bergson’s lattermost great writing, defines the universe as “a machine of making gods”. This thesis — although it was announced after a diligent consideration of the religions and of the mysticism — is not, however, a conclusion derived solely from this mentioned analysis. The image of the universe as a factory of making gods, as we intend to demonstrate, was already developed in L’évolution créatrice, and the conclusions obtained in this essay, published in 1907, are what sustain Bergson’s conception of universe. Nevertheless, identifying its essential function is something that L’évolution créatrice could not have made completely and neither would Les deux sources de la morale et de la religion if its origin were not in the preceding work.
The factory of gods: the universe and its essential function in Henri Bergson's philosophy
Keywords: Evolução; Universo; Consciência; Criação; Evolution; Universe; Consciousness; Creation; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA; CIENCIAS HUMANAS::FILOSOFIA::METAFISICA